Testing a multiple reference station GPS network for real-time carrier-phase-based positioning in the Marmara region, Turkey - Dogan, U; Alves, P; Lachapelle, G; Ergintav, S (TAYLOR & FRANCIS LTD, 2004)
A network of multiple ground-based, continuous GPS reference stations for generating carriers phase-based corrections can provide a higher achievable position accuracy, and increase the speed and effectiveness of carrier phase integer ambiguity resolution for precise real-time positioning in relation to the traditional single baseline approach. This method also allows,for a lower number of reference stations required to cover a larger service area than the traditional single reference station approach. The focus of this paper is to investigate the multiple reference station method for generating carriers phase-based corrections using the Marmara Continuous GPS Network, Turkey. The carrier phase measurement corrections for the coverage area are computed using the NetAdjust method, developed at the University of Calgary. Results and analysis using the regional carrier-phase corrections are compared to the single reference receiver approach to demonstrate the achievable improvement with this method. The results show 55 to 75 percent improvement in the observation domain, 40 to 60 percent improvement in the real-time position accuracy, and an 11 to 38 percent decrease in the time required to resolve L1 ambiguities. The corresponding position accuracies for a user's receiver show as much as 58, 45, and 35 percent improvement in the latitude, longitude and height, respectively, over the single baseline approach.
Keywords: Engineering; Geology; Remote Sensing